THE FAMILY'S PERCEPTIONS REGARDING THE CHILD'S DIFFICULTIES ADAPTING TO HOSPITALIZATION: SUPPORT FOR THE NURSING - Giovana Calcagno Gomes; Glaucia Dal Omo Nicola; Nathalia Zinn de Souza; Maria Cristina da Silveira Chagas; Dóris Farias Ribeiro Farias; Daiani Modernel Xavier (Universidade Federal do Paraná, 2013)
This exploratory-descriptive research with a qualitative approach was based in the methodological framework of Grounded Theory, and aimed to investigate the family's perceptions regarding the child's difficulties in adapting, during coping with hospitalization. The participants were 15 families providing care and data collection was undertaken in the first semester of 2010, through semi-structured interviews. Based on the content of these, the researchers proceeded to open, axial and selective codification. Three categories were identified: the hospital environment as different, the child's fear of hospitalization, and changes in the child's behavior. It is concluded that it is necessary to support the family, so that it may give the necessary support to the child in hospital and care in a humanized way, such that the hospitalization may be less traumatic.